A multipoint problem for partial differential equations unresolved with respect to the higher time derivative - Klyus, I. S.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the well-posedness of problems for partial differential equations unresolved with respect to the higher time derivative with multipoint conditions with respect to time. By using the metric approach, we determine lower bounds for small denominators appearing in the course of the solution of the problems.